A Unique Case of Diffuse Metastatic Neuroendocrine Cancer with Subcutaneous Nodules on 18-F-Fluorodeoxyglucose Positron Emission Tomography/Computer Assisted Tomography - Mickaila Johnston; Archana Sachedina; James McDonald (World Journal of Nuclear Medicine)
Neuroendocrine tumors (NETs) account for 8-10% of cases of carcinomas of unknown primary. Most of these cases are poorly differentiated with metastatic disease at the time of diagnosis. However, cutaneous metastatic presentation is rare. We present an interesting case of a 74-year-old woman presenting with cutaneous metastatic involvement from high grade poorly differentiated NET of unknown origin. She was referred to us with a diagnosis of lymphoma. 18-F-fluorodeoxyglucose positron emission tomography/computer assisted tomography imaging at our institution offered a differential diagnosis, including neuroendocrine cancer. Repeat skin lesion biopsy demonstrated "non-Merkel cell" carcinoma, favoring metastatic high-grade neuroendocrine carcinoma.